Plan estratégico para la comercialización de productos agroecológicos de la microempresa H&H Nutripac del cantón Loja - Jaramillo Cueva, Diego Fernando (2024)
The current trends of the population oriented to the consumption of a sustainable food diet have generated a growing demand for agroecological production, for this reason, the objective of this research was to develop a strategic plan for the marketing of agroecological products produced under greenhouse of the microenterprise H&H Nutripac located in the Loja canton, which allows it to satisfactorily supply its current demand and expand the customer base. The methodology of the study is transversal, mixed with a descriptive scope; the survey technique was applied to 384 people from Loja between 18 and 64 years of age to know the level of acceptance and consumption of agroecological products in the sector, in addition, an interview was conducted with the legal representative of the microenterprise and government authorities with competence in the agricultural sector of Loja canton. The results showed that 81.5% of Loja families do consume agroecological products, but 51.3% do not know the products offered by H&H Nutripac, which explains the low level of commercialization of the microenterprise. Based on this, a strategic plan was developed containing: mission, vision, institutional values, improvement strategies, and an annual operating plan. Finally, it is recommended to carry out periodic evaluations to measure the level of customer satisfaction; focus on the promotion and dissemination of the products offered and implement the proposed strategic plan in order to generate positive changes that encourage the growth and competitiveness of H&H Nutripac in the local market.